2005
DOI: 10.1287/orsc.1050.0151
|View full text |Cite
|
Sign up to set email alerts
|

Identities, Genres, and Organizational Forms

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
434
1
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 455 publications
(448 citation statements)
references
References 73 publications
6
434
1
7
Order By: Relevance
“…Research on organizational identities suggests that the engagement of producers indicates a credible commitment towards the claimed identity should be rewarded by a target audience (Hannan et al, 2007;Hsu and Hannan, 2005;Carroll and Swaminathan, 2000). In our setting, cooperation among MUs represented a credible commitment to their collective identity.…”
Section: Variations In Organizational Engagementmentioning
confidence: 77%
“…Research on organizational identities suggests that the engagement of producers indicates a credible commitment towards the claimed identity should be rewarded by a target audience (Hannan et al, 2007;Hsu and Hannan, 2005;Carroll and Swaminathan, 2000). In our setting, cooperation among MUs represented a credible commitment to their collective identity.…”
Section: Variations In Organizational Engagementmentioning
confidence: 77%
“…In sociological perspective, an organization's identity is given by an audience (Zuckerman 1999;Hsu and Hannan 2005;Hannan, Pólos, and Carroll 2007). Audience structure affects consensus formation and corresponding processes of identity formation and interaction (Hannan, Pólos, and Carroll 2007).…”
Section: External Audiences: Foreigners and Enthusiastsmentioning
confidence: 99%
“…Increased organizational density within a sector contributes to overcoming the liability of newness and increasing legitimacy (Carroll and Hannan, 1989;Hannan et al, 1995;McKendrick and Carroll, 2001): "density is a parsimonious indicator of legitimacy that enjoys predictability for a remarkably wide array of organizations" (Deephouse and Suchman, 2008, p. 55). Density alone, however, is not enough to secure legitimacy; the public must have knowledge of the organizations and be able to recognize and categorize them (Hsu and Hannan, 2005;McKendrick et al, 2003;Navis and Glynn, 2010). Prior studies have found that organizations engage in strategies to increase public recognition and gain legitimacy (for example, Suchman, 1995;Scherer et al, 2013;Tornikoski and Newbert, 2007;Zimmerman and Zeitz, 2002).…”
Section: Legitimation Strategiesmentioning
confidence: 99%